Предмет: Алгебра,
автор: poddubskaya03
Замените выражение М многочленом так, чтобы получилось тождество: а) М + (3ху - 2у2) = х2 + ху - у2
б) М - (4ху + 3у2) = х2 + ху - у2
Ответы
Автор ответа:
0
а) М+(3ху-2у²)=х²+ху-у²
(х²-2ху+у²)+(3ху-2у²)=х²+ху-у²
б) М-(4ху+3у²)= х²+ху-у²
(х²+5ху+2у²)-(4ху+3у²)= х²+ху-у²
Похожие вопросы
Предмет: Биология,
автор: ninokal212009
Предмет: Алгебра,
автор: ucinaliza
Предмет: Информатика,
автор: denisenkoivan68
Предмет: Математика,
автор: siergieisolovi
Предмет: Химия,
автор: Аноним